The Dream Stealer - Fleischman, Sid, 1920-2010.; d (New York, N.Y. : Greenwillow Books, 2009)
A plucky Mexican girl tries to recover her dream from the Dream Stealer who takes her to his castle where countless dreams and even more adventures await.
A Junior Library Guild selection
Grades 4 up.
Keywords: Dreams -- Juvenile fiction; Animals, Mythical -- Juvenile fiction; Mexico -- Juvenile fiction; Dreams -- Fiction; Imaginary creatures -- Fiction; Mexico -- Fiction